DRAMATURGICALCONCEPTION FOR THEPROCCESSOFTEACHING - Chotimah, Ima Chusnul (STKIP PGRI Jombang, 2014)
This study was conducted based on the level of the needs toward class‟smastery forteachers.Classmasterybecomesimportantfortheidealteaching-learning process.Theteacherswouldseemunprofessionalwhentheyarenotabletomasterthe class.From thisphenomenon,theresearchermadeaformulationby integratingseveral conceptsofclassmastery,bothpsychologically anddramaturgicallybecomeoneterm called